Modernizing public services: subtle interplays of politics and management. Issue 4 (7th November 2016) - Arnaboldi, Michela; Lapsley, Irvine; Dal Molin, Martina
Abstract : Purpose: This paper aims to examine the trajectory of public management reforms in Italy. This experience indicates the complexity of managerialism in countries with a legalistic system and where public administration cultures have been, and continue to be, embedded in politics. Design/methodology/approach: The analysis of managerial reforms in Italy was carried out with a documentary analysis. In addition to official reports and acts of parliament, the analysis was based on monitoring the government websites and innovative channels (e.g. Facebook) which communicated the progress of the later reforms. Findings: The paper shows how modernization of public services has been a continuous priority in the agenda of the Italian Government across four phases: an early attempt in the late 1970s; a lively, phase for Italian managerial reforms in the 1990s; a later advocacy in the 2000s of a specific new public management (NPM) element – performance management; an after-crises reform aimed at reducing public expenditure. Originality/value: The paper takes a historical and long-term perspective to analyse the success and failure of NPM reforms implementation in Italy. Differently from previous studies, this papers analyses NPM reforms in a longitudinal perspective, to show how the legalistic culture of Italy continues to affect the implementation of NPM reforms.